The rhythm of the night: patterns of activity of the European wildcat in the Italian peninsula - Lorenzo Lazzeri; Paola Fazzi; Marco Lucchesi; Emiliano Mori; Edoardo Velli; Nadia Cappai; Francesca Ciuti; Francesco Ferretti; Federica Fonda; Chiara Paniccia; Marco Pavanello; Stefano Pecorella; et al. (Mammalian Biology, 2022)
The European wildcat is a threatened carnivore, whose ecology is still scarcely studied, especially in Mediterranean areas. In this study, we estimated activity rhythm patterns of this felid, by means of camera-trapping at three spatial scales: (i) whole country (Italy); (ii) biogeographical areas; (iii) latitudinal zones. The activity rhythms patterns were also calculated according to temporal scales: (1) warm semester; (2) cold semester and (3) seasonal scales. Lastly, we also tested whether the effect of moon phases affected the wildcat activity. We conducted the analysis on a total of 975 independent events collected in 2009–2021, from 285 locations, in ~ 65,800 camera days. We showed that the wildcat in Italy exhibits a > 70% nocturnal behaviour, with 20% of diurnal activity, at all spatial scales, and throughout the whole year, with peaks at 10.00 p.m. and 04.00 a.m. We observed a high overlap of wildcat activity rhythms between different biogeographical and latitudinal zones. The wildcat was mainly active on the darkest nights, reducing its activity in bright moonlight nights. Diurnal activity was greater in the warm months and decreased with the distance from shrubs and woodlands, most likely according to activity rhythms of its main prey, water presence in summer, the care of offspring and the availability of shelter sites. Conversely, the distance to paved roads seems to have no significant effects on diurnal activity, suggesting that, in presence of natural shelters, the wildcat probably may tolerate these infrastructures. We suggested limited plasticity in activity rhythm patterns of the wildcat, emphasizing the importance of dark hours for this species.